RIOH BALAK - Ira Puspita Sari S1 (Saraswati)
The writing with title “Rioh Balak dance” meaning frenzied people who are doing illegal logging. The writing tells us about story of illegal logging is now often the case in every area of ​​Indonesia. Rampant illegal logging going on, especially in Riau inspired to create a work of dance with theme illegal logging. Starting from the view of a paper mill with the raw material is natural wood, that’s make the writer asked if a factory used employment system illegal logging or not. With what has been experienced the writer because of the impact of illegal logging is burning of forest that’s make smoke so thick that cause illness, respiratory distress. The selection of the theme of illegal logging in this dance work certainly has some important goals for both writer, society and environment. One of those goals is to invite, to bring people to always preserve the environment, preservation of forests because forests provide a very useful source of life for us. Indonesian forest area vast stretches from Sabang to Marauke often referred to as the emerald equator which has an important role on the global ecological balance, and even Indonesia's tropical forests are considered as the lungs of the world that have a central role to life and living beings in the world.